TRANSFORMASI POLA PERMUKIMAN PESISIR PASCA TSUNAMI DI KECAMATAN TAWAELI KOTA PALU - Takwim, Supriadi; Eisenring, Deltri Dikwardi; Winarta, Ardiansyah; Khaerunnisa, Khaerunnisa; Maghfirah, Fitriah Fajar (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
Coastal settlements in Tawaeli District, Palu, were severely damaged by the earthquake and tsunami of September 28, 2018, making it necessary to examine the transformation of spatial patterns and their implications for safer settlement planning. This study aims to identify changes in coastal settlement patterns before and after the tsunami, analyze the associated socio-economic impacts, evaluate the effectiveness of mitigation and spatial planning policies, and assess forms of community resilience and adaptation strategies. A descriptive–exploratory qualitative approach was employed, supported by spatial analysis. Primary data were obtained through in-depth interviews with affected residents, community leaders, and technical officials, as well as field observations and participatory mapping. Secondary data were derived from multi-temporal satellite imagery, tsunami hazard zoning maps, and planning documents such as spatial plans and detailed spatial plans, along with relevant institutional reports. The results show that prior to the tsunami, coastal settlements in Tawaeli were predominantly characterized by a linear pattern following the coastline and main roads. After the disaster, a mixed pattern emerged, including partial retreat from coastal zones, the development of permanent housing clusters in hilly areas, and self-reconstruction in certain coastal segments. Spatial planning policies have incorporated tsunami hazard considerations through the designation of high-risk zones; however, their implementation remains partial and not yet fully aligned with livelihood needs. Communities have responded through various adaptation strategies, including building modifications, gradual relocation, and livelihood diversification. This study concludes that the transformation of coastal settlement patterns in Tawaeli is the result of an interaction between disaster pressures, spatial planning policies, and community agency. Therefore, post-disaster spatial planning should simultaneously integrate risk reduction, livelihood sustainability, and the strengthening of community resilience.